Notes on the Lewis Chessmen (Proceedings of the Society of Antiquaries of Scotland, 1863)
Captain Thomas relates a story from local Lewis folklore about how the Lewis Chessmen came to be buried in Uig bay. Although he suggests that there is a possibility that this account is somewhat accurate, he also acknowledges that this legend does not explain where the Lewis Chessmen originated.